Biocultural and nutritional significance of Sauromatum diversifolium in Central Himalayan communities, India - RAJPAL SINGH NEGI; V. K. PUROHIT; R. K. MAIKHURI; VINOD NAUTIYAL; SUBHASH CHANDRA; LAKHPAT SINGH RAWAT; M. C. NAUTIYAL; SUDEEP CHANDRA; RAVINDRA SINGH (Society for Indonesian Biodiversity, 2025)
Abstract. Negi RS, Purohit VK, Maikhuri RK, Nautiyal V, Chandra S, Rawat LS, Nautiyal MC, Chandra S, Singh R. 2025. Biocultural and nutritional significance of Sauromatum diversifolium in Central Himalayan Communities, India. Biodiversitas 26: 4023-4034. Sauromatum diversifolium, locally known as Nagdoon, is one of the important underutilized wild edible plant species whose root tuber (corm) is locally used as a staple food and a traditional medicine among indigenous communities in the Central Himalaya, Uttarakhand, India. Despite its significant cultural and medicinal importance, S. diversifolium remains largely under-researched, highlighting the urgent need to revalidate its traditional uses and explore its nutraceutical potential. The present study aims to analyze the nutritional value of the tuber and document the Indigenous knowledge related to local food, healthcare practices, biocultural traditions, and the socio-religious values of S. diversifolium in the Uttarakhand, namely Rawain, Niti, Darma, and Byans valleys of the region. An ethnobotanical survey using Participatory Rural Approaches (PRA), inventories, interviews, and local discussions in five villages (277 households) of Rawain Valley, followed by the collection of S. diversifolium for phytochemical and nutraceutical analysis of its tubers. The results of the nutritional analysis revealed the high nutritional value of the tubers, with significant levels of vitamins (B2, C, E), proteins, carbohydrates, and minerals were analyzed to understand their nutritional potential. The results revealed that the boiled tubers of the plant are traditionally consumed as a healthy food and used for medicinal purposes to treat various diseases, as reported by 95% respondents. The chemical screening of the corm showed higher Vitamin C content (4.7 mg/g) than other vitamins. Additionally, the carbohydrate, potassium, and calcium contents were also found significantly higher (76.6, 850, and 213 mg/100 g, respectively). The species can be a potential source of high-value food and provide an additional source of income opportunities for indigenous/ traditional communities. The present study emphasizes the domestication, large-scale cultivation, value addition, and product development of the species to enhance livelihoods and income generation, ensuring the sustainability of socio-ecological systems and the biocultural conservation of the region.